Pharmaceutical Innovations: Artificial Intelligence and Scientific Cooperation as the Certain Future for the Pharmaceutical Industry - L. I. Shcherbakova; P. P. Rodionov (Регуляторные исследования и экспертиза лекарственных средств)
Today, the pharmaceutical industry is on the cusp of a “digital renaissance”, where artificial intelligence (AI) and science complement each other. The use of bioinformatics, machine learning, and AI unlocks new opportunities for optimising all stages of the medicinal product lifecycle and reducing the time and costs of drug development. Engaging in joint initiatives with academic institutions, which have consolidated the infrastructure for fundamental research, contributes significantly to the development of innovative medicinal products and shortens the research and development timelines. For drug developers selecting a direction for biological target identification, it is of importance to follow the vectors of national projects, which aim to foster technological sovereignty in the manufacturing of pharmaceuticals, advanced therapy medicinal products, and medical devices. This publication is a paired interview with Lyudmila I. Shcherbakova, President of Velpharm Group, and Pyotr P. Rodionov, General Director of GEROPHARM. In this interview, they analyse key technology trends shaping the landscape of the pharmaceutical industry and discuss current trends and prospects in drug development, such as the use of AI.